Malawi : Request for a One-Year Exogenous Shocks Facility Arrangement; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Malawi. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses a request from Malawi for a one-year exogenous shocks facility (ESF) arrangement to help it adjust to the large terms-of-trade shock it has suffered. Real GDP growth of Malawi has been high and is expected to remain solid. Inflation, though rising in recent months, is still moderate and is expected to ease over the medium term. The government's near-term program aims to increase the import coverage of official gross reserves while preserving growth and food security. IMF staff supports the authorities' request for a one-year high-access ESF arrangement.